Development of a Molecularly Imprinted Polymer-based electrochemical biosensor for the detection of Spike Protein in SARS-CoV-2 - Monteiro, Rita Cristina Soares de Brito Vieira (2022)
Trabalho de Projeto do Mestrado Integrado em Engenharia Biomédica apresentado à Faculdade de Ciências e Tecnologia